Improving patient‐centred care through a tailored intervention addressing nursing clinical handover communication in its organizational and cultural context. (17th January 2022) - Chien, Laura J.; Slade, Diana; Dahm, Maria R.; Brady, Bernadette; Roberts, Elizabeth; Goncharov, Liza; Taylor, Joanne; Eggins, Suzanne; Thornton, Anna
Abstract: Aims: To increase the quality and safety of patient care, many hospitals have mandated that nursing clinical handover occur at the patient's bedside. This study aims to improve the patient‐centredness of nursing handover by addressing the communication challenges of bedside handover and the organizational and cultural practices that shape handover. Design: Qualitative linguistic ethnographic design combining discourse analysis of actual handover interactions and interviews and focus groups before and after a tailored intervention. Methods: Pre‐intervention we conducted interviews with nursing, medical and allied health staff ( n = 14) and focus groups with nurses and students ( n = 13) in one hospital's Rehabilitation ward. We recorded handovers ( n = 16) and multidisciplinary team huddles ( n = 3). An intervention of communication training and recommendations for organizational and cultural change was delivered to staff and championed by ward management. After the intervention we interviewed nurses and recorded and analyzed handovers. Data were collected from February to August 2020. Ward management collected hospital‐acquired complication data. Results: Notable changes post‐intervention included a shift to involve patients in bedside handovers, improved ward‐level communication and culture, and an associated decrease in reported hospital‐acquired complications. Conclusions: Effective change in handover practices is achieved through communication training combined with redesign of local practices inhibiting patient‐centred handovers. Strong leadership to champion change, ongoing mentoring and reinforcement of new practices, and collaboration with nurses throughout the change process were critical to success. Impact: Ineffective communication during handover jeopardizes patient safety and limits patient involvement. Our targeted, locally designed communication intervention significantly improved handover practices and patient involvement through the use of informational and interactional protocols, and redesigned handover tools and meetings. Our approach promoted a ward culture that prioritizes patient‐centred care and patient safety. This innovative intervention resulted in an associated decrease in hospital‐acquired complications. The intervention has been rolled out to a further five wards across two hospitals.